The Amphipathic GM1 Molecule Stabilizes Amyloid Aggregates, Preventing their Cytotoxicity - Bucciantini, Monica (Biophys J, 2020)
Amyloid aggregates have been demonstrated to exert cytotoxic effects in several diseases. It is widely accepted that the complex and fascinating aggregation pathway involves a series of steps during which many heterogeneous intermediates are generated. This process may be greatly potentiated by the presence of amphipathic components of plasma membrane because they may serve as interaction, condensation, and nucleation points. However, there are few data regarding structural alterations induced by the binding between the amyloid fibrils and membrane components and its direct effects on cell integrity. In this study, we found, by 1-anilinonaphthalene 8-sulfonic acid and transmission electron microscopy/fast Fourier transform, that yeast prion Sup35 oligomers showed higher structural uniformity and altered surface properties when grown in the presence of monosialotetrahexosylganglioside, a component of the cell membrane. 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide and confocal/sensitized Förster resonance energy transfer analyses revealed that these fibrils showed low cytotoxicity and affinity to plasma membrane. Moreover, time-lapse analysis of Sup35 oligomer fibrillation on cells suggested that the amyloid aggregation process per se exerts cytotoxic effects through the interaction of amyloid intermediates with plasma membrane components. These data provide, to our knowledge, new insights to understand the mechanism of amyloid growth and cytotoxicity in the pathogenesis of amyloid diseases.